3 Proceedings of the Council of Maryland, 1636-1667, at 345 (reprint 1965) - (:unkn) unknown (My University, 1658)
Required that captains make "a perfect list" of "all persons able to beare Armes within theyr respective divisions that is of all men betweene 16 and 60 yeares of Age."
Keywords: MILITIAS